Innovation and Implementation of Online Learning Technology in Enhancing Learning Experience Post-COVID-19 - Dajang, Innocent Nasuk; Ayuba, Mandong Mathias; Mahanan, Samuel (International Journal of Environment, Engineering and Education, 2024)
Recently, especially with the COVID-19 experience, the need to deploy technology in education has taken center stage. Before the pandemic, many teachers did not particularly consider the use of technology as a valuable resource for teaching and learning. However, this is rapidly beginning to change. Many languages programmed in the country are now experimenting with and utilizing technology in learning. Appropriate use of these new resources has effectively upgraded language instruction and learning. Much time, effort, and money has been spent researching and implementing new and existing technology to improve language training. Twenty-five language educators, in a focus group session conducted, feel that now is the time when the use of technological resources to enhance the learning experience will offer the highly motivated learner an efficient and flexible means of attaining basic communicative competence in language learning. The paper discusses how technology can facilitate learning in language teaching. The paper discusses the need to use some technologies for language teaching, like Zoom, Google Meet, Teams, YouTube, and Facebook, which can be easily accessible to computers, iPads, and Android devices. The research notes that with modern technology, one can learn without necessarily being in the physical classroom. Modern language teaching and learning technology makes learning easily accessible anytime and anywhere, provided internet connectivity exists.